Health-Related Quality of Life and Related Factors in Thais with Stable COPD - NOONIL, Naiyana; PETSIRASAN, Rewwadee; AEKWARANGKOON, Saifon (Walailak Journal of Science and Technology (WJST), 2018)
This cross-sectional descriptive study aimed to describe the health-related quality of life (HRQL) and related factors of the southern Thai patients with stable COPD. The sample consisted of 126 patients with stable COPD attending the out-patient pulmonary clinic of Thasala hospital. The patients were assessed for HRQL by the Saint George's Respiratory Questionnaire (SGRQ), age, BMI, depression, dyspnea by the Modified Medical Research Council (mMRC), exercise capacity by the 6 min walk distance (6MWD), and admission. The results found that 84 % of patients were male, with a mean age of 69.6 years, FEV1 70 (9.6) % predicted, BMI 21.9 (4.4) and 6MWD 259.8 (97.9). The HRQL indicated mild impairment: symptoms 47.1 (22.4), activity 49.7 (30.3), impact 41.9 (21.2) and total scores of 45.1 (21.7). The regression analysis showed that HRQL was significantly associated with exercise capacity, depression, and MRC dyspnea respectively (R2 = 0.492, p < 0.01). Therefore, stable COPD patients should be assessed and motivated to pulmonary rehabilitation for promoting clinical outcomes and also improving their HRQL.